Avidin inhibits PHA-induced human peripheral blood mononuclear cell proliferation (Faculty of Medicine Universitas Indonesia, 2016)
Background: Cell proliferation occurs not only in normal but also in cancer cells. Most of cell proliferation inhibition can be done by inhibiting the DNA synthesis, notably by intervening the formation of purine or pyrimidine. In purine de novo synthesis, it was assumed that biotin plays a role as a coenzyme in carboxylation reaction, one of the pivotal steps in the purine de novo pathways. The aim of this study was to see the avidin potency to bind biotin and inhibit mitosis.Methods: Peripheral blood mononuclear cell (PBMC) was cultured in RPMI-1640 medium and stimulated by phytohemagglutinin (PHA) in the presence or absence of interleukin-2 (IL-2), with or without avidin. The effect of avidin addition was observed at 24, 48, and 72 hours for cell proliferation, viability, and cell cycle. Statistical analysis was done by one-way ANOVA.Results: Avidin inhibited cell proliferation and viability in culture under stimulation by PHA with and without IL-2. Cell cycle analysis showed that avidin arrested the progression of PBMC after 72 hours of culture. Most cells were found in G0/G1 phase.Conclusion: Inhibition of biotin utilization by avidin binding can halt cell proliferation.